2013
DOI: 10.1016/j.socscimed.2013.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Becoming and remaining community health workers: Perspectives from Ethiopia and Mozambique

Abstract: Many global health practitioners are currently reaffirming the importance of recruiting and retaining effective community health workers (CHWs) in order to achieve major public health goals. This raises policy-relevant questions about why people become and remain CHWs. This paper addresses these questions, drawing on ethnographic work in Addis Ababa, the capital of Ethiopia, between 2006 and 2009, and in Chimoio, a provincial town in central Mozambique, between 2003 and 2010. Participant observation and in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 37 publications
5
124
0
Order By: Relevance
“…Swartz and Colvin [59] suggest that the lack of payment is reflective of a broader, gendered, and structural lack of recognition of the female workforce. The requirement of a fair wage and a secure livelihood is the leading philosophical argument in favour of a paid workforce [7,14]. We provide data that such a philosophy would also have benefits for child recipients of care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Swartz and Colvin [59] suggest that the lack of payment is reflective of a broader, gendered, and structural lack of recognition of the female workforce. The requirement of a fair wage and a secure livelihood is the leading philosophical argument in favour of a paid workforce [7,14]. We provide data that such a philosophy would also have benefits for child recipients of care.…”
Section: Discussionmentioning
confidence: 99%
“…Countries that use this model include Malawi [6], Ethiopia [7], Zambia [8], South Africa [9], India [10], and Nepal [11]. It has been estimated that there are approximately 60 000 CHWs now working in South Africa [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars in health policy and systems research (HPSR) are increasingly interested in understanding more about how international health priorities affect individuals responsible for executing carrying them out (Sheikh et al 2014). For example, research from medical anthropology has demonstrated the difficulties faced by community health workers in Ethiopia (Maes and Kalofonos 2013) and healthcare providers in Malawi (Rosenthal 2015) working in HIV/AIDS programs. Despite the fact that nurses, as frontline health workers, are key actors in carrying out policy directives, research on how they understand policy or respond to policy change in their professional lives is largely underrepresented in the HPSR literature (Richter et al 2013, Juma et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many sub-Saharan countries have scaled-up CHW interventions especially in rural and remote areas (Maes & Kalofonos, 2013). The Ugandan government began implementing its CHW strategy in 2001 through Village Health Teams (VHTs)-a group of volunteers at the village level trained to become the "vehicle" through which interventions would reach local communities.…”
mentioning
confidence: 99%